Immunoglobulin heavy chain locus of the rat: striking homology to mouse antibody genes. - Brüggemann, M (1986)
DNA encoding the rat diversity segment (D), joining segment (JH), and constant (C) region mu, gamma 2a, gamma 1, gamma 2b, epsilon and alpha of the Ig heavy chain has been isolated from a cosmid library. Restriction mapping allowed us to identify two gene clusters: D-JH-C mu and C gamma 1-C gamma 2b-C epsilon-C alpha in addition to a single C gamma 2a gene. Analysis of genomic DNA by Southern blotting permitted identification of the C gamma 2c gene and led to the proposal of the following gene order for the rat Ig heavy chain locus: D-JH-C mu-C delta-(C gamma 2c, C gamma 2a)-C gamma 1-C gamma 2b-C epsilon-C alpha. There is striking homology between the rat and mouse Ig heavy chain loci as regards gene order and distance between CH genes. Partial DNA sequencing confirms this homology and shows that exon sequences are more conserved than are intron sequences. One of the most conserved intron regions between rat and mouse is that spanning the Ig heavy chain enhancer (91% homology). However, the relationship between the different C gamma subclasses in rat differs from that in mouse. Comparison of the C gamma CH3 domains shows that the rat C gamma 2b gene is most homologous to mouse C gamma 2a/b, whereas the rat C gamma 1 and C gamma 2a genes, both very similar to each other, are most homologous to the mouse C gamma 1 gene.